Peculiarities of dispersion characteristics of sinusoidally rippled plasma waveguides with small ripple depth - Lapshin, V.I.; Tkachenko, V.I.; Tkachenko, I.V. (Вопросы атомной науки и техники, 2003)
Analytical expressions for the dispersion equations of E-waves of flat and cylindrical sinusoidal rippled plasma waveguides with super conducting walls in a strong external magnetic field are received. Origin of forbidden bands, which are formed at crossings of the dispersion curves describing various own modes, is investigated. The width of formed forbidden bands and group speeds of own waves near to the forbidden bands are determined. Comparison of the theory with results of the previous researches in special cases gives good qualitative and quantitative conformity. Отримано аналітичні вирази для дисперсійних рівнянь Е-хвиль плоского і циліндричного плазмових хвилеводів з сінусоідально гофрованими ідеально провідними стінками в сильному зовнішньому магнітному полі. Досліджено утворення смуг непрозорості, які утворюються при перетинанні дисперсійних кривих, що характеризують різноманітні власні моди. Визначено ширину смуг непрозорості, що утворюються, і групові швидкості власних хвиль поблизу смуг непрозорості. Порівняння теорії з результатами попередніх досліджень в окремих випадках дає гарну якісну і кількісну відповідність. Получены аналитические выражения для дисперсионных уравнений Е-волн плоского и цилиндрического плазменных волноводов с синусоидально гофрированными идеально проводящими стенками в сильном внешнем магнитном поле. Исследовано образование полос непрозрачности, которые образуются при пересечении дисперсионных кривых, характеризующих различные собственные моды. Определены ширина образующихся полос непрозрачности и групповые скорости собственных волн вблизи полос непрозрачности. Сравнение теории с результатами предыдущих исследований в частных случаях дает хорошее качественное и количественное соответствие.